2020
DOI: 10.1177/0020872820905350
|View full text |Cite
|
Sign up to set email alerts
|

Do stress and coping influence resilience in social work students? A longitudinal and comparative study from India

Abstract: Stress among social work students is an issue of concern and has adverse outcomes. This study used a longitudinal design to assess stress, resilience and coping in undergraduate social work students in India and a comparative cohort of non-social work undergraduates. Standardised instruments were administered at three time points: the first on course entry, then in the second year of study and finally on the verge of course completion at the end of three years. Moderate levels of stress and resilience were see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
2
0
0
Order By: Relevance
“…Students who scored higher on the PSS-10 measuring perceived stress were more likely to have difficulty surviving (low resilience score). This finding is in line with Stanley & Mettilda Buvaneswari's (2020) research findings revealed that stress levels negatively affect the manifestation of resilience. Recent research also supports a negative relationship between stress and resilience (Melguizo-Ibáñez et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Students who scored higher on the PSS-10 measuring perceived stress were more likely to have difficulty surviving (low resilience score). This finding is in line with Stanley & Mettilda Buvaneswari's (2020) research findings revealed that stress levels negatively affect the manifestation of resilience. Recent research also supports a negative relationship between stress and resilience (Melguizo-Ibáñez et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…One explanation for the finding of that study might be because adult students may get strength and support from their accumulated roles as an adult, and from their educators followed by the expectations and demands of class work and academic performance. In addition, another study that is similar to the current study which is by Stanley and Buvaneswari (2020) revealed that the level of resilience among social work students are moderate.…”
Section: Discussionsupporting
confidence: 79%